ANALISIS SISTEM PENDIDIKAN ISLAM DI NEGERI MULLAH REPUBLIK ISLAM IRAN - Haris Riadi; Johan Andriesgo (STAIN Bengkalis, 2019)
After the 1979 Islamic Revolution, Iran was a country that declared itself as an authoritative Islamic Republic. Long before, Iran became the heir to the tradition of Islamic philosophy. Iran is also the center of Shia, a group that claims to base its Ahlul Bayt tradition. No wonder that eventually Iran became an important center of world Islamic civilization. Various acts of this country in the religion of Islam, many are used as references for Muslims in other parts of the world. In this article, we discuss how Iran manages Islamic education. In addition to describing many things about education, such as the education system, education gap, and education funding, the author also compares Islamic education in the Gulf state with Islamic education in Indonesia. Today, after the revolution led by Ayatullah Khomaini on 11 February 1979, which was not only limited in terms of governance but also in the field of Islamic education, the Iranian nation has gained much progress in various fields, especially in the fields of science and technology.Pasca-Revolusi Islam tahun 1979, Iran adalah negera yang mendeklarasikan diri sebagai Negara Republik Islam yang otoritatif. Jauh sebelumnya, Iran menjadi pewaris tradisi filsafat Islam. Iran juga merupakan pusat Syiah, sebuah kelompok yang mengaku mendasarkan pada tradisi ahlul bayt. Tak heran jika akhirnya Iran menjadi pusat peradaban Islam dunia yang penting. Berbagai kiprah negara ini dalam beragama Islam, banyak dijadikan referensi bagi umat Islam di belahan dunia lain. Dalam artikel ini, didiskusikan bagaimana Iran mengelola pendidikan Islam. Selain memaparkan banyak hal tentang pendidikan, seperti sistem pendidikan, perjenjangan pendidikan, dan pembiayaan pendidikan, penulis juga membandingkan antara pendidikan Islam di negara Teluk tersebut dengan pendidikan Islam di Indonesia. Dewasa ini, setelah revolusi yang dipimpin oleh Ayatullah Khomaini pada 11 Pebruari 1979, yang tidak hanya terbatas dalam aspek pemerintahan tetapi juga dalam bidang pendidikan Islam, bangsa Iran telah memperoleh banyak kemajuan dalam berbagai bidang, terutama bidang ilmu pengetahuan dan teknologi.___________________Keywords: Pendidikan Islam, Iran, Kurikulum.